Dietary krill meal inclusion contributes to better growth performance of gilthead seabream juveniles. (26th July 2018) - Saleh, Reda; Burri, Lena; Benitez‐Santana, Tibiabin; Turkmen, Serhat; Castro, Pedro; Izquierdo, Marisol
Abstract: There is a need to find sustainable alternatives to fishmeal (FM) and fish oil (FO) in feed formulations to support the continued growth of aquaculture. FM is mostly produced from mass‐caught pelagic species, but the production has been relatively constant for several decades. The aim of this study was to investigate the potential of dietary krill meal (KM) inclusion as a sustainable alternative to FM. In view of that, a feeding trial with gilthead seabream juveniles was conducted to evaluate whether dietary KM at 3%, 6% and 9% inclusion improves growth performance in comparison with a control diet. At the end of the study, fish in the 9% KM group showed significantly higher body weight (32.76 g) compared with fish fed the control diet (30.30 g). Moreover, FM replacement by 9% KM indicated a reduction in the accumulation of lipid droplets in the hepatocytes and around the pancreatic islets. In summary, this study suggests that FM can be reduced in diets for seabream without negatively affecting growth performance, when KM is added. On the contrary, KM enhances gilthead seabream growth and reduces lipid accumulation and damage of hepatocytes, which will open an interesting innovation line to completely replace FM by alternative terrestrial protein sources and the partial inclusion of KM.